Acrylamide formation in air-fried versus deep and oven-fried potatoes - Navruz-Varlı, Semra; Mortaş, Hande (Frontiers in Nutrition, 2024)
Introduction: Present study investigates the effects of different home pre-treatment processes and cooking techniques on the acrylamide content of fried potatoes.Methods: Potato sticks were prepared in two different pre-treatment ways (washing and soaking) and cooked with three other techniques (air frying, deep frying, and oven frying). Acrylamide analyses were performed on cooked potatoes using an LC-MS/MS method.The highest acrylamide content was found in potatoes cooked using the air fryer (12.19±7.03 µg/kg). This was followed by deep frying (8.94±9.21 µg/kg) and oven frying (7.43±3.75 µg/kg). However, the difference between the acrylamide contents of the potatoes according to the cooking methods was not statistically significant. The acrylamide content of the potatoes that were subjected to soaking in all three ways was lower than the potatoes that were not soaked and only washed. In the deep-frying method, it was found statistically significant that the soaked potatoes contained less acrylamide (p=0.029).Discussion: It is important to highlight the relatively low acrylamide levels found in ovenfrying, lower than air frying in both washing and soaking groups in the present study. Although air fryers, which have become widely used as an alternative to deep frying in recent years, provide french fries with less oil, their role in the formation of acrylamide should be further investigated.